(untitled) (Research, Society and Development, 2020)
Wireless sensor networks have been applied extensively in home and industrial automation. The objective of this project is to develop a wireless sensor network with Mesh topology using the ZigBee protocol. For the development of the research used a case study, where there is a description of the elaboration of devices and development of a wireless sensor network. The network is equipped with coordinating devices, routers and an end device. As a result, the network was tested in order to validate the ability to restructure and self-organize the Mesh topology based on the protocol used.